Development of Mathematics Integrated Science basic Concept Module about Classification Things to Improve Understanding of PGSD Students - Yanti Fitria; Aissy Putri Zulkarnaini (International Journal of Educational Dynamics, 2022)
This study aims to develop a Mathematics Integrated Science Basic Concept Module with a user guide to improve student understanding and the level of use by lecturers and students. The development method used is the ADDIE model. The feasibility test was carried out by three content experts, three design experts, and the usability test was carried out by three science lecturers. Product trials were conducted on second-semester students of UPP IV Bukittinggi majoring in PGSD, Universitas Negeri Padang. The instruments used were the Likert scale and a questionnaire. The data collected in this study were analyzed using descriptive statistical analysis and non-parametric statistical analysis. The findings of this study indicate that the developed module is very feasible from the aspect of module content with a percentage of 94.5% and the aspect of module display with a percentage of 85.6%. The results of the Kendall's W concordance coefficient test for experts from the aspects of the content and appearance of the module along with the guidelines for its use, it is known that there is a harmonious assessment given between the experts. The results of the usability test assessment show that the assessment given by science lecturers is in the Very Good (VG) category with a percentage of 89.1%. This means that the developed module can be operationalized by science lecturers as a relevant medium in giving lectures on basic science concepts related to understanding the classification of living things. Furthermore, from the results of the Kendall Concordance coefficient test, it is known that there is an alignment of the assessments given by the three science lecturers. The usability test was also carried out on students and the results were in the Very Good (VG) category with a percentage of 91.5%. This shows that the developed modules can be used by PGSD students and their guides by lecturers. This means that students can understand the module components being developed in terms of usability, language use, appearance, and attractiveness as well as module content. Then, the results of Kendall's W concordance coefficient test showed that there was an alignment of the assessments given by students and lecturers. Based on these results, in general, it can be concluded that the developed modules are appropriate and can be used to assist students in increasing their understanding of the classification of living things integrated with groups.